Percutaneous Translaminar Facet Cyst Rupture and Epidural Access—Description of a Novel Technique. Issue 3 (14th March 2017) - Spinner, David; Aner, Moris; Paul, Geet; Simopoulos, Thomas; Gill, Jatinder
Abstract: Synovial cysts of the lumbar zygapophysial joints can be treated by percutaneous injection of corticosteroids, with distension and rupture of the cyst. Some cysts can be difficult to access, particularly when they lie deep in relation to the lamina. This technical report describes a fluoroscopy-guided technique for accessing sublaminar pathology. Crucial to the safety of the technique is visualization of the ventral margin of the lamina using a contralateral oblique view, and controlling and limiting the insertion of the needle such that only its tip passes the lamina.